Causes and consequences of the process of soil salinization - Pedrotti, Alceu; Chagas, Rogério Moreira; Ramos, Victor Callegari; Prata, Ana Paula do Nascimento; Lucas, Ariovaldo Antônio Tadeu; Santos, Pricila Barbosa dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The process of soil salinization is typical of arid and semi-arid regions, often resulting from the combination of geological formation predominant in the landscape, poor distribution of rainfall, poor drainage and inadequate farm. The exploitation of natural resources with the use of inadequate techniques has favored the increase of the degree of degradation, because they affect agricultural production and the environment, causing a number of problems of social and political order. One area can remain saline during years with low or moderate salinity, unless the problem is detected. A further increase in the salt content can cause cessation of agricultural land in a few years since higher amounts of salts in the soil cause changes in the physical characteristics of the soils and slows or prevents the growth of plants, mainly due to increased osmotic potential and indirect toxicity of certain elements. Strategies such as the use of extracting plants, the use of gypsum and lime as the use of techniques to improve drainage of the soil, are adopted for reclamation by excess salts, and that when applied together can minimize the deleterious effects of excess salts in soil.